Formulation of Carrageenan and Sodium Chloride in Edible Coatings for Enhanced Tilapia Fillet Preservation - Pamungkas, Amin; Hakim, Arif R; Fauzi, Ahmat; Sedayu, Bakti B; Wullandari, Putri; Siregar, Zaenal Arifin (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2025)
While carrageenan coatings offer promising preservation for fish, limitations like water absorption and insufficient antimicrobial strength necessitate more investigation on combining them with natural substances. This study aimed to extend the shelf life of tilapia fillets using an edible coating made from carrageenan and sodium chloride (NaCl). Response Surface Methodology (RSM) was employed to optimize the coating formulation, considering film properties such as thickness, swelling index, opacity, and water vapor transfer rate. A Central Composite Design (CCD) identified the optimal composition as 1.4 grams of carrageenan and 0.6 grams of NaCl, minimizing undesirable characteristics. The optimized coating was applied to fresh tilapia fillets and compared to uncoated controls during five days of refrigerated storage (4.5 oC). Quality parameters, including bacterial count, total volatile basic nitrogen (TVB-N), pH, weight loss, and color, were monitored. The carrageenan-NaCl coating significantly reduced bacterial growth, with values increasing from log 6.31 CFU/ml on day 0 to log 6.34 CFU/ml on day 5, compared to uncoated fillets exhibiting TNTC (too numerous to count) bacteria by the end of storage. Additionally, the coated fillets displayed a lower increase in TVB-N (22.50%) compared to uncoated samples (31.38%), maintaining a stable pH and experiencing less weight loss (27.54%) compared to uncoated controls (32.96%). The coating also effectively preserved color, indicating its potential to maintain sensory attributes. These findings suggest that the optimized carrageenan-NaCl edible coating offers a promising strategy for extending the shelf life and maintaining the quality of fresh tilapia fillets, potentially reducing losses within the seafood supply chain.